Validation of the five-tier Taiwan Triage and Acuity Scale for prehospital use by Emergency Medical Technicians. Issue 8 (29th July 2019) - Ng, Chip-Jin; Chien, Cheng-Yu; Seak, Julian Chen-June; Tsai, Shang-Li; Weng, Yi-Ming; Chaou, Chung-Hsien; Kuo, Chan-Wei; Chen, Jih-Chang; Hsu, Kuang-Hung
Abstract : Objectives: This study aimed to determine the inter-rater reliability of the five-level Taiwan Triage and Acuity Scale (TTAS) when used by emergency medical technicians (EMTs) and triage registered nurses (TRNs). Furthermore, it sought to validate the prehospital TTAS scores according to ED hospitalisation rates and medical resource consumption. Methods: This was a prospective observational study. After training in five-level triage, EMTs triaged patients arriving to the ED and agreement with the nurse triage (TRN) was assessed. Subsequently, these trained research EMTs rode along on ambulance calls and assigned TTAS scores for each patient at the scene, while the on-duty EMTs applied their standard two-tier prehospital triage scale and followed standard practice, blinded to the TTAS scores. The accuracy of the TTAS scores in the field for prediction of hospitalisation and medical resource consumption were analysed using logistic regression and a linear model, respectively, and compared with the accuracy of the current two-tier prehospital triage scale. Results: After EMT's underwent initial training in five-level TTAS, inter-rater agreement between EMTs and TRNs for triage of ED patients was very good (κw=0.825, CI 0.750 to 0.900). For the outcome of hospitalisation, TTAS five-level system (Akaike's Information Criteria (AIC)=486, area under the curve (AUC)=0.75) showed better discrimination compared with TPTS two-level system (AIC=508, AUC=0.66). Triage assignments by the EMTs using the the five-level TTAS was linearly associated with hospitalisation and medical resource consumption. Conclusions: A five-level prehospital triage scale shows good inter-rater reliability and superior discrimination compared with the two-level system for prediction of hospitalisation and medical resource requirements.